Pedagogical Conditions and Structural-Functional Model of Formation of Subject-Methodical Competence of Future Teachers of Physical Education in Institutions of Higher Education of Ukraine - Yana Yeremiia (Pedagogical Discourse, 2023)
The article highlights pedagogical conditions and characterizes the structural-functional model of formation of subject-methodical competence of future physical education teachers. The system-forming component of the pedagogical activity of a modern physical culture teacher is subject-methodical activity, which, on the one hand, is connected with teaching methods, on the other - with ideas about pedagogical activity, in the genesis of which specific actions aimed at construction, selection appear and the use of these methods as ways of organizing the educational and recreational activities of schoolchildren by the teacher. In the author's understanding, the process of professional and pedagogical training takes place in the environment of higher education institutions, in which the student exists and is formed as a person, masters the skills of pedagogical activity and develops in himself the qualities and attributes of the personality that are significant for this profession. It is assumed that the generated pedagogical conditions will qualitatively improve the functioning of students in the educational environment of higher education institutions. Separate pedagogical conditions constitute the space of the educational process in which a student can self-regulate and self-educate himself as a subject of subject-methodical professional activity in accordance with the requirements of the teaching profession and his capabilities.Summarized, the list of pedagogical conditions that, potentially, will effectively influence the dynamics of the formation of the subject-methodical competence of future physical education teachers (ensuring professional motivation of students for methodologically appropriate professional activities to preserve and strengthen the health of students; expanding and updating the content of the training of future physical education teachers of culture in order to systematize the subject-methodical knowledge of students; the creation of a practice-oriented subject environment for the training of future physical education teachers; the organization of pedagogical support for the self-education of students regarding the creation of their own subject-methodical educational products). The structural-functional model of the process of forming the subject-methodical competence of future physical culture teachers in the educational process of higher education is a means aimed at realizing the goal of the study. The proposed model consists of five blocks, each of which has a corresponding functional load (target, theoretical-methodological, content-technological, control-analytical and is characterized by the interconnection of all its structural elements and reflects the complex implementation of all pedagogical conditions determined in the study.